EFFECT OF A REHABILITATIVE EXERCISES PROGRAM WITH USING THERAPEUTIC MASSAGE, AND ELECTRICAL STIMULATION TO RESTORE THE EFFICIENCY OF ROTARY CUFF MUSCLES OF THE SHOULDER JOINT FOR JUNIORS DOLPHIN SWIMMERS (Journal of Pharmaceutical Negative Results, 2023)
The research aims to identify the effect of Rehabilitation Exercises Program With Use of Therapeutic Massage, Electrical Stimulation to Restore the Efficiency of the Rotator Cuff Muscles of the Shoulder Joint for Dolphin Swimmers, and this is achieved through the following subobjectives: Developing the muscle strength of the muscle groups working on the shoulder joint, improving the flexibility of the shoulder joint by increasing the range of motion in the positive direction (flexion and extension), reducing the degree of pain caused by inflammation of the shoulder joint, The experimental method was used in the experimental design of one group by applying Pre and Post measurements, and the research sample was chosen intentionally from young dolphins swimming with pain in the shoulder joint in Dakahlia Governorate, and those who frequented the fitness centers At Mansoura Sports Stadium, numbering (10) juniors and their ages range from 10 Between (13-15) years old and registered in Egyptian Swimming Federation for the 2021/2022 training season, Homogeneity was performed on the research sample in the basic measurements (age, height, weight, training age, arm length, shoulder width, body mass index), as well as homogeneity in the variables of muscle strength, shoulder joint flexibility and pain degree for the sample under investigation, The most important results indicated that the rehabilitation exercise program that includes strength and flexibility training with the use of therapeutic massage and the proposed electrical stimulation led to the development of balanced muscle strength of the working (motor) and opposite (reverse) muscles near the affected shoulder joint, as well as increasing the range of motion of the shoulder joint for dolphin swimmers in It also helped reduce the sensation of pain in the affected shoulder joint, and restore the relative recovery of the rotator muscles affected by inflammation in the shoulder joint of dolphin swimmers , The researchers recommend the need to educate injured swimmers to undergo rehabilitation sports programs after injury, as it helps them to return quickly to practice specialized sports activity as soon as possible and at a level close to their level before the injury .